JURNAL SKRIPSI PROGRAM PELAYANAN DAN REHABILITASI SOSIAL BAGI PENGEMIS, GELANDANGAN DAN ORANG TELANTAR DI BALAI REHABILITASI SOSIAL â€œMARDI UTOMOâ€ SEMARANG TAHUN 2011-2014 - Ulfa, Rayanis Maria; Adhi, Suwanto; Manar, D Ghulam (Journal of Politic and Government Studies, 2016)
This study was conducted to explain the Social and Rehabilitation Services Program for beggars and abandoned children in the Mardi UtomoSocial Rehabilitation Center Semarang. The Social Rehabilitation Center is a Technical Implementation Unit Provincial Social Service of Central Java as one of the institutions Social and Rehabilitation Services for productive adults who specifically is directed with social welfare problems Beggars homeless and internally displaced persons. There is one of the activities that have not been implemented to the preparation activities social environment which includes the preparation of a family environment, the preparation around the lives of clients or beneficiaries (neighbors, peers, village governments and local communities) the preparation of the social environment client widely (schools, businesses, etc.) However, in the implementation for the Beggars homeless and internally displaced persons well in accordance with the Operational Service Standards. They are able to increase the degree of wellfare, able to live independently in the midst of a better society and able to carry out a social function naturally. In Sumarry existence of Mardi UtomoSocial Rehabilitation Center Semarang has been participating in reducing social welfare problems in Central Java Province. Keywords: Social and Rehabilitation Services of social welfare problems in the Mardi UtomoSocial Rehabilitation Center Semarang.